Elektrokardiogram športnikov - Ažman-Juvan, Katja (Zdravniški vestnik, 2010)
Electrocardiogram (ECG) is being increasingly used as part of cardiovascular preparticipation screening of young competitive athletes (under 35 years of age) since it significantly increases the sensitivity of such screening compared to history and clinical examination alone. It has become part of a common European protocol for cardiovascular preparticipation screening of young competitive athletes. For a proper interpretation of ECG changes, it is crucial to be familiar with ECG abnormalities in cardiovascular diseases causing sudden cardiac death, and with normal variants of athletećs ECG, originating from their adaptations to intense athletic training. Structural adaptations (increased heart chamber size and mass) often result in isolated voltage criterion for left ventricular hypertrophy and incomplete right bundlebranch block, while functional adaptations (mainly heightened parasympathetic tone) result in rhythm disorders (sinus bradycardia, pauses and arrhythmia, wandering atrial pacemaker), conduction abnormalities (atrioventricular block grade I and grade II Mobitz 1) and repolarization abnormalities (early repolarization, T wave changes). The article gives a detailed description of ECG changes in the athletećs heart and in cardiovascular diseases responsible for most sudden cardiac deaths in young athletes.
Keywords: Aritmija; Arrhythmia; Bradikardija; Bradycardia; Cardiomyopathy, Hypertrophic; cardiovascular disease; Death, Sudden, Cardiac; diagnostika; Electrocardiography; Elektrokardiografija; Kardiomiopatija hipertrofična; kardiovaskularne bolezni; Long Qt Syndrome; Podaljšana doba QT, sindrom; preventivna medicina; Smrt nenadna, srčna; Sports; Športi; športniki; Wolff-Parkinson-White Syndrome; Wolff-Parkinson-Whiteov sindrom